A note on the superstring BRST operator - Acosta, José N. [UNESP]; Berkovits, Nathan [UNESP]; Chandia, Osvaldo [UNESP] (Elsevier, 1999)
We write the BRST operator of the N = 1 superstring as, Q = e-R(1/2πiφdzγ2b)eR where y and b are super-reparameterization ghosts. This provides a trivial proof that Q is nilpotent. © 1999 Published by Elsevier Science B.V. All rights reserved.